MANAJEMEN LABA DAN PENYEBABNYA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI - Riza Fauziyah, Firliy (Soetomo Accounting Review, 2024)
When profits are manipulated, companies face ramifications, most notably in the eyes of the general public and potential investors. The focus of this study is on how financial distress, tax strategy, and company size influence earnings management in connection to managerial ownership. Focusing on technology companies listed on the Indonesia Stock Exchange between 2018 and 2022, this research uses a quantitative approach. A convenience sample of 35 firms was selected for this study using a systematic selection technique. The dependent variable in this study is earnings management; the independent variables are financial distress, tax approach, and firm size; and the moderating variable is managerial ownership. The statistical analysis in this research was performed using the Partial Least Square (PLS) method, which was implemented in SmartPLS 3.0. The study found that earnings management was not affected by factors like financial distress or tax strategy, but that firm size had a significant negative impact (at the 5% level of significance). Earnings management is still vulnerable to external factors including financial distress, tax strategy, and firm size, which are all unaffected by managerial ownership.